Relationship between two stimulation techniques of chromatic pupillometry - Tripolone, María Constanza (2021)
It has been proposed that flickering pupil light reflex (fPLR) can give information about the transient component of pulsed pupil light reflex (pPLR). Based on this assumption, parameters for the transient part of the pPLR (initial constriction and time to minimum) should be related to the parameters of the fPLR (amplitude and phase). We correlated parameters from fPLR with those from pPLR. A Newtonian view arrangement used in this study was composed by a lab-made photostimulator-pupillometer system. We obtained pupillary recordings for Blue, Cyan, Green and Red stimuli conditions. 15 observers with normal vision participated. For the fPLR, sinusoidal stimuli of 1Hz were used. For the pPLR, the stimuli were rectangular pulses. Positive correlations were obtained for initial constriction vs amplitude for all stimuli condition. Instead, for time to minimum vs phase no correlation was found. Thus, parameters considering the transient constriction intensity were related. However, temporal parameters were not associated, except for Red stimuli.